Pengaruh Strategi Pemasaran, Biaya Pemasaran, Fluktuasi Harga, Dan Saluran Distribusi Terhadap Profitabilitas Perusahaan: (Studi Kasus Peron Mitra Baru Di Perusahaan Perkebunan Kelapa Sawit Di Riau) - Febri Lia Safitri; M. Trihudiyatmanto; Ratna Wijayanti (Journal of Economics, Management, and Business, 2026)
Purpose – This study aims to analyze the influence of marketing strategy, marketing costs, price fluctuations, and distribution channels on company profitability at Peron Mitra Baru in a palm oil plantation company in Riau. Methodology – This study employed a quantitative method with a descriptive approach. The population consisted of 215 oil palm farmers, with a sample of 70 respondents determined using the Isaac and Michael formula and selected through Simple Random Sampling. Data were collected using questionnaires and analyzed using multiple linear regression. Findings – The results showed that marketing strategy, marketing costs, price fluctuations, and distribution channels simultaneously had a significant effect on company profitability (F = 158.391; Sig. = 0.000). Partially, marketing costs and distribution channels had a positive and significant effect on company profitability, while marketing strategy and price fluctuations had no significant effect. The Adjusted R Square value of 0.901 indicates that the independent variables explained 90.1% of the variation in company profitability, while the remaining 9.9% was influenced by other factors outside the study. Limitations – This study was conducted in only one palm oil plantation company in Riau with a limited number of respondents, which may restrict the generalizability of the findings. Future Research Agenda – Future studies are recommended to include additional variables affecting company profitability, such as product quality, sales volume, customer satisfaction, and market conditions, as well as expand the research scope to obtain more comprehensive results.